2016
DOI: 10.1136/jramc-2015-000600
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of military head injuries

Abstract: The description of body segment varies among articles and this makes comparisons among datasets difficult. There is a lack of detail regarding the precise position and severity of injuries, and long-term outcome for casualties. It is demonstrated that wearing military helmets reduces fatalities on and off the battlefield. The risk of BHBT injuries is widely referred to, but evidence of their occurrence is not provided by the authors that describe the risk of BHBT occurring. Further research into the causes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Ballistic head injury is complex and outcome is influenced by many factors [ 1 4 ]. Wearing military helmets is associated with reduced fatalities from ballistic impact [ 2 ]. Mechanisms include projectile deflection and energy dissipation by the helmet materials, although above a particular impact energy, the helmet materials will be defeated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ballistic head injury is complex and outcome is influenced by many factors [ 1 4 ]. Wearing military helmets is associated with reduced fatalities from ballistic impact [ 2 ]. Mechanisms include projectile deflection and energy dissipation by the helmet materials, although above a particular impact energy, the helmet materials will be defeated.…”
Section: Discussionmentioning
confidence: 99%
“…Ballistic head injury remains a significant threat in combat [ 1 ]. A recent review of the open access literature [ 2 ] concluded that fatal head injuries are mainly from bullets overmatching helmets or fragments penetrating through the face. The authors also stated the need for further research into the causes and severity of head injury to assist designers of military helmets and associated personal protective equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Ballistic head injury is a significant threat to troops in combat [ 1 ] and ongoing research is needed to assist designers of military helmets and associated personal protective equipment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…У систематичному огляді ЧМТ, отриманих під час військових дій, було проаналізовано 40 літературних джерел із проблем вогнепальних ЧМП [8]. Проте автори наголошують на складності отримання вірогідних даних про частоту, характер вогнепальних поранень та результати лікування.…”
Section: вступunclassified